Comparative genomics, pangenomics, and phenomic studies of Pectobacterium betavasculorum strains isolated from sugar beet, potato, sunflower, and artichoke: insights into pathogenicity, virulence determinants, and adaptation to the host plant - Borowska-Beszta, Maria; Smoktunowicz, Magdalena; Horoszkiewicz, Daria; Jonca, Joanna; Waleron, Michal Mateusz; Gawor, Jan; Mika, Adriana; Sledzinski, Tomasz; Waleron, Krzysztof; Waleron, Malgorzata (Frontiers in Plant Science, 2024)
Pectobacterium is the genus that gathers the species of economically essential pathogens of various plants. P. betavasculorum species was formerly thought to infect beetroots. However, their host range is far broader. It causes sunflower, potato, tomato, carrots, sweet potato, radish, squash, cucumber, and chrysanthemum diseases. To explain this phenomenon, a comprehensive pathogenomic and phenomic characterisation of P. betavasculorum species was performed. Genomes of strains isolated from potato, sunflower and artichoke were sequenced and compared with genomes of strains isolated from sugar beet. The genome size ranged from 4.675 to 4.931 kbp, and GC % was between 51.0%-51.2%. The pangenome of P. betavasculorum is open and comprises, on average, 4220 gene families. Of these, 83% of genes are the core genome, and 2% of the entire pangenome are unique genes. Strains isolated from sugar beet have a smaller pangenome size and a higher number of unique genes than those from other plants. Interestingly, genomes of strains from artichoke and sunflower share 391 common CDS that are not present in the genomes of other strains from sugar beet or potato. Those strains have only one unique gene. The metabolic profiling of P. betavasculorum confirmed that all strains could use numerous sugars as a building material and energy source. Pathogenomics analysis indicates the presence of a high repertoire of virulence determinants in the P. betavasculorum genomes. The in silico predicted ability of P. betavasculorum strains to cause disease symptoms under laboratory conditions was confirmed with pathogenicity assays on potato tubers and chicory leaves. Their ability to synthesise homoserine lactones, siderophores, bacteriocins and plant hormones was also proven with various assays. P. betavasculorum strains possess a marked adaptation potential to the plant host and environmental faintness. Strains adapted to plants with high sugar content in tissues have a different composition of fatty acids in membranes and a different mechanism of replenishing nitrogen in case of deficiency of this biogen than strains derived from other plant species. Extensive phenomics and genomic analyses performed in this study have shown that P. betavasculorum species is an agronomically relevant pathogen.